Advertising Analysis of Hotel Businesses in Terms of Digital Visual Culture - Yapıcı, Olcay Ozısık; Büyükkaragöz, Tahir (My University, 2023)
The purpose of this paper is to examine the hotel advertisements broadcast on YouTube in different continents in terms of digital visual culture. The ads on the YouTube page of the hotel companies were analyzed by semiotics method. The use of technology, the quality of service and the sense of trust were prioritized as a result of semiotic analysis of the advertising films on the YouTube pages of the hotel company located in 3 countries located on different continents. According to findings, the local tastes and cultural values, as well as the outdoor attractiveness of the countries in which they are located among the common points of the commercials in terms of digital visual culture. In addition to the short duration of the commercials presented by the hotels via YouTube, there are also messages related to the selected target market. With the widespread use of information and communication technologies, hotel businesses take their place on social media and different platforms. Hotel businesses in the tourism sector should use social platforms extensively in order to compete, to increase their market share and to ensure customer satisfaction. Promotional images and commercial films prepared on social platforms should be made by considering market segmentation. Hotel businesses should not forget that the visual culture is digitalized in the commercials they use on social platforms.
Keywords: Otelcilik; Konaklama; Spor ve Turizm; İletişim; Bilgi; Belge Yönetimi; Görüntüleme Bilimi ve Fotoğraf Teknolojisi